Neurocognitive Biotypes of Risk and Resilience for Mood Disorders in Adolescents: Insights From Behavioral and Graph-Theoretic Network Markers - Ambra Coccaro; Ziwei Cheng; Luka Ruzic; Amelia D. Moser; Jenna Jones; Elena C. Peterson; Elisa F. Stern; Naomi P. Friedman; Roselinde H. Kaiser (Biological Psychiatry Global Open Science)
Background: Adolescence is a developmental period of increased prevalence of mood disorders, but identifying adolescents who are at risk for or resilient to mood pathology remains a clinical challenge. In the current study, we addressed this challenge by evaluating multidimensional profiles of neurocognitive functioning (biotypes) that may confer vulnerability or protect against psychopathology. Biotypes were derived from neurocognitive data and identified as being resilient or high risk based on their association with future symptoms. Methods: Adolescents (N = 146; 13–21 years, 66% first-degree familial history of mood disorders) completed behavioral tests and magnetic resonance imaging at baseline. Biotypes were derived using cluster analysis on measures of reward sensitivity and executive functioning. Over 2 years, participants reported on subjective life stress and symptoms of anhedonia or mania/hypomania. Regression analyses were used to test biotype differences in symptom variability (lability in mood symptoms) and life stress as a moderator of biotype-related differences. Results: Biotype 1 (high executive functions, balanced integration/segregation of functional brain networks) was resilient: adolescents in this biotype reported low symptom variability, even under heightened life stress. Adolescents in biotype 2 (poor executive functions, low frontoparietal modularity) reported higher variability in symptoms of mania/hypomania overall. Adolescents in biotype 3 (mixed reward sensitivity, high overall network modularity) reported high variability in symptoms of anhedonia and mania/hypomania, if also reporting heightened life stress. Adolescents in biotype 4 (blunted reward decision processing, hyperconnected networks) reported high variability in symptoms of anhedonia, if also reporting heightened life stress. Conclusions: Neurocognitive biotypes may identify adolescents who are resilient to, or at risk for, mood pathology.